فاعلية برنامج إرشادي انتقائي في تنمية مهارات ابعاد الذكاء الروحي وفق نموذج (ويجلس ورث، Wigglesworth) لدى الموهوبين من طلبة الجامعة (Revue El-Wahat pour les Recherches et les Etudes, 2023)
ملخص:هدفت الدراسة اختبار فعالية برنامج أرشادي انتقائي في تنمية مهارات أبعاد الذكاء الروحي، وفقًا للنموذج الذي اقترحه ويجلس ورث (2006) لدى الطلاب الموهوبين. تكون مجتمع الدراسة من (320) طالباً موهوباً من جامعة مؤتة في الأردن. تكونت العينة من 30 طالبًا موهوبًا تتراوح أعمارهم بين 18 - 22 عامًا. تبنت الدراسة المنهج  شبه التجريبي ذو المجموعتين التجريبية والضابطة. تم بناء مقياس الذكاء الروحي من (36) فقرة موزعة على الابعاد الخمسة لنموذج (ويجلس ورث، 2006). كما تم بناء البرنامج الإرشادي من (11) جلسة إرشادية وجلسة متابعة واحدة. أظهرت النتائج وجود فروق دالة إحصائياً في ابعاد الذكاء الروحي المتمثلة في "النظرة الإيجابية والسمو الذاتي، الإدراك الواعي لمعنى الحياة، التأمل في طبيعة الكون، الممارسات السلوكية الروحية، إدراك المعاناة كفرصة" بين متوسط درجات القياس القبلي والبعدي للمجموعة التجريبية لصالح القياس البعدي. وظهرت فروق بين متوسطي درجات المجموعتين التجريبية والضابطة لصالح المجموعة التجريبية وهذا ما يؤكد فاعلية البرنامج الإرشادي في تعزيز مهارات الذكاء الروحي. إلا أن الفروق لم تكن ذات دلالة إحصائية بين القياس البعدي والقياس التتبعي للمجموعة التجريبية، مما يدل على استمرارية فاعلية البرنامج الإرشادي بعد فترة المتابعة. وأوصت الدراسة بتبني البرنامج الإرشادي من قبل الاخصائيين النفسين في المؤسسات التربوية، والاستفادة من ادوات الدراسة في دراسات مماثلة في مجتمعات بحثية أخرى.كلمات دالة: الفاعلية، برنامج الإرشاد الانتقائي، الذكاء الروحي، الموهوبونAbstract: The Effectiveness of a Selective Counseling Program in Developing the Skills of piritual Intelligence Dimensions, According to Wigglesworth's Model, among Talented Studentsthis study investigates the effectiveness of a selective counseling program to developing the skills of spiritual intelligence dimensions according to the model proposed by Wigglesworth (2006) among talented students. The study population consists of (320) talented students from Mutah University in Jordan. The sample consisted of 30 talented students, aged 18-22 years.  The study adopts the Semi- experimental method that has the experimental and control groups. The scale of spiritual intelligence was constructed from (36) statements distributed over the five dimensions of the model (Wigglesworth, 2006).  counseling program was also constructed of (11) counseling sessions and one follow-up session. , the results showed that there were differences In the dimensions of spiritual intelligence "Positive outlook and self-transcendence, conscious realization of  the meaning of life, meditation on the nature of the universe, spiritual behavioral practices, realizing suffering as an opportunity" between the average grades of the pre and post measurements of the experimental group favoring the post measurement.  and differences appeared   between the average grades of the experimental and control groups favoring the experimental group, and this confirms the effectiveness of the program. However, the differences were not significant between the post and follow-up measurements of the experimental group, which indicates the continuity of the effectiveness of the counseling program after the follow-up period. The study recommended the adoption of the counseling program for similar studies in other research communities. Keywords: effectiveness, selective counseling program, spiritual intelligence, gifted students